1-(N-phenylamino)naphthalene oligomers as novel hole transport materials for highly efficient green electrophosphorescence. (July 2015) - Zhang, Song; Xue, Li-Sha; Jing, Yi-Ming; Liu, Xuan; Lu, Guang-Zhao; Liang, Xiao; Li, Hong-Yan; Zheng, You-Xuan; Zuo, Jing-Lin
Abstract: Two hole transport materials, N -(4-carbazol-9-yl-phenyl)- N ′-naphthalen-1-yl- N, N ′- diphenyl-naphthalene-1, 4-diamine and N -(4-carbazol-9-yl-phenyl)- N ′-(4- N, N - phenyl-naphthalene-naphthalen-1-yl)- N, N ′-diphenyl-naphthalene-1, 4-diamine, were synthesized by the addition of a carbazole moiety on to the dimer or trimer of N -phenyl-1-naphthylamine. Both of these hole transport materials have high glass transition temperatures of 135 and 167 °C, respectively. The green phosphorescent organic light-emitting diodes (PHOLEDs) of ITO (indium tin oxide)/new hole transport material (50 nm)/Ir(tfmppy)2 (tpip) (tfmppy = 4-trifluoromethylphenyl-pyridine, tpip = tetraphenylimidodiphosphinate, 8 wt%): mCP ( N, N ′-dicarbazolyl-3, 5-benzene, 25 nm)/TmPyPB (1, 3, 5-trim-pyrid-3-yl-phenyl)benzene, 50 nm)/LiF (1 nm)/Al (100 nm) exhibit high efficiency (maximum current efficiency ( η c, max ) of 113.9 and 108.8 cd A −1, maximum external quantum efficiency (EQE) of 29.8% and 28.5%, respectively) with a low efficiency roll-off. At 3000 cd m −2 brightness, the ηc values still remain as high as 109.3 and 105.3 cd A −1, respectively. The device performances proved that these new materials derived from N -phenyl-1-naphthylamine would be promising hole transport materials for PHOLEDs. Graphical abstract: Two hole transport materials were synthesized, the dimer (CZ-NPNA2 ) and trimer (CZ-NPNA3 ) of N -phenyl-1-naphthylamine. Highly efficient OLEDs (ηc, max of −113.9 cd/A, ηp, max of −67.5 lm/W and EQEmax of 29.8% forCZ-NPNA2 ; ηc, max of −108.8 cd/A, ηp, max of −53.6 lm/W and EQEmax of 28.5% forCZ-NPNA3 ) are fabricated with low efficiency roll-off ratios. Highlights: Two new hole transport materials were synthesised. The materials show high glass transition temperatures. The derived OLEDs exhibit high efficiencies. The efficiency roll-off ratios are low for all devices.